Barusida Math Sebagai Aplikasi Media Pembelajaran Matematika Bangun Ruang Sisi Datar Berbasis Android - Wanti Rahayu; Ari Irawan (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
The low level of students' understanding of the flat side space requires learning media that can support learning activities so that it is necessary to make android-based learning media. The purpose of this research is to create an application "Barusida Math" that can help students to better understand the material of flat-sided shapes. The method used in this research is Research and Development (RnD) using the ADDIE approach (Analysis, Design, Development, Implementation and Evaluation). The instruments in data collection were interviews, observations, pre-research questionnaires, literature studies, learning media validation questionnaires, learning media guide book validation questionnaires, student and teacher response questionnaires. The results of this research are in the form of a mathematics learning application "Barusida Math" which can be used as a medium for learning mathematics for flat-sided geometry at the junior high school or madrasah tsanawiah level. Currently the research is still in the development stage where it is still available offline. In the future the team plans to validate, test the effectiveness, and practicality of the "Barusida Math" application. The steps that will be carried out in the future are the implementation and evaluation of the ADDIE model used in the stages of this research activity.